Analisis Kompensasi dan Inklusi Keuangan Terhadap Kesejahteraan Rumah Tangga Involuntary Resettlement di Desa Pongkai Istiqomah dan Koto Masjid Kecamatan XIII Koto Kampar Propinsi Riau - M. Gunawan Azhar; Fery Andrianus; Neng Kamarni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
This study examines how compensation and financial inclusion influence the welfare of involuntary resettlement households in the villages of Pongkai Istiqomah and Koto Masjid. The formulation of the problem is how compensation and financial inclusion affect the welfare of households in Pongkai Istiqomah and Koto Masjid villages due to the involuntary resettlement program and how does compensation affect the financial inclusion of households in Pongkai Istiqomah and Koto Masjid villages who were moved due to the involuntary resettlement program. Based on the formulation of the problem that has been packaged, the objectives of this study are as follows, to analyze the effect of compensation and financial inclusion on household welfare in the villages of Pongkai Istiqomah and Koto Masji and to analyze the effect of compensation on financial inclusion in the villages of Pongkai Istiqomah and Koto Masjid which were moved due to the involuntary resettlement program . The methodology in this study uses the mix method, namely by using qualitative analysis by conducting interviews with involuntary resettlement households in the villages of Pongkai Istiqomah and Koto Masjid with regard to the welfare of their households. And the next analysis uses quantitative analysis using SEM (Structural Equation) analysis using the Stata 15.0 application, namely analyzing compensation and financial inclusion on the welfare of the community in the villages of Pongkai Istiqomah and Koto Masjid, and analyzing the effect of compensation on financial inclusion. In this study, researchers found that there was a significant relationship between compensation and financial inclusion on community welfare in Pongkai Istiqomah and Koto Masjid villages, while there was no significant relationship between compensation and financial inclusion. Other factors that affect the level of welfare in the two villages are the mindset of the community and the social environment of the community.